Volume 5: 37th Design Automation Conference, Parts a and B 2011
DOI: 10.1115/detc2011-48409
|View full text |Cite
|
Sign up to set email alerts
|

Robust Design for Profit Maximization Under Uncertainty of Consumer Choice Model Parameters Using the Delta Method

Abstract: In new product design, risk averse firms must consider downside risk in addition to expected profitability, since some designs are associated with greater market uncertainty than others. We propose an approach to robust optimal product design for profit maximization by introducing an α-profit metric to manage expected profitability vs. downside risk due to uncertainty in market share predictions. Our goal is to maximize profit at a firm-specified level of risk tolerance. Specifically, we find the design that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…First-order analysis of uncertainties, which is also known as the Delta method, is a rather straightforward and useful technique for the approximation of such uncertainties. This method is widely used in many fields of engineering due mainly to its ease of application to a wide variety of problems [17][18][19]. Mays stated that Delta method application is quite popular in many fields of engineering and, as a result, he developed a risk-based solution for storm sewers' design [17].…”
Section: Analysis Of Uncertainty (Delta Method)mentioning
confidence: 99%
See 1 more Smart Citation
“…First-order analysis of uncertainties, which is also known as the Delta method, is a rather straightforward and useful technique for the approximation of such uncertainties. This method is widely used in many fields of engineering due mainly to its ease of application to a wide variety of problems [17][18][19]. Mays stated that Delta method application is quite popular in many fields of engineering and, as a result, he developed a risk-based solution for storm sewers' design [17].…”
Section: Analysis Of Uncertainty (Delta Method)mentioning
confidence: 99%
“…Their research showed that the average TSI number and its variation for mentioned reservoir oscillated between Mesotrophic to Eutrophic category [18]. Furthermore, Resende et al applied Delta method to estimate the mapping, from uncertainty in discrete choice model parameters to uncertainty of profit outcomes, and they identified the estimated -profit as a closed form function of design decision variables in computer science [19].…”
Section: Analysis Of Uncertainty (Delta Method)mentioning
confidence: 99%
“…The Gumbel distribution is used to approximate closely normal distribution and yields a closed-form solution that leads to a computational advantage [194,195]. In summary, the MNL is applied to this study because of its advantages such as simplicity, interpretability, and its capability of extending the choice probability into new product design development [194,196,199].…”
Section: Modelling Customer Preference and Expected Demandmentioning
confidence: 99%